The Attitudes and Practices of General Practitioners about the Use of Chaperones in Melbourne, Australia. - van Hecke, O; Jones, K (2012)
Introduction. To consider the use of medical chaperones during certain clinical examinations is important whether one practises as a specialist, nurse, medical student, or generalist. Chaperones have been used by doctors conducting intimate examinations for many years but their true extent remains largely unknown. Until recently, there was no national guidance in Australia. Aim. To explore the attitudes and practices of general practitioners (GP) regarding their use of chaperones in urban Melbourne, Australia. Method. Qualitative two focus groups involving seventeen GPs from two locations. Discussions were audio-taped, transcribed verbatim and analysed. Results. Common themes and subthemes emerged which were grouped into three main areas: (a) practitioner-related, (b) patient-related and (c) practice related. Discussion. This is the first study from an Australian primary care perspective to gauge the attitudes and experiences of GPs on their use of chaperones. It will provide vital information to inform the next step of extending this research to a national GP audience. From an international perspective, this study provides an excellent template for other primary care clinicians to conduct research in this important field of doctor-patient relationship.